They, you, I: Fictionality and the Greenlandic suicide situation in Niviaq Korneliussen’s Blomsterdalen - Meyer, Pernille (Nordlit, 2024)
In this article, I analyse Niviaq Korneliussen’s treatment of the current Greenlandic suicide situation in the novel Flower Valley (Blomsterdalen, 2020). The novel is – according to the author – «political», which raises several questions: Why write a novel instead of an opinion piece? What possibilities does fiction open? In what ways can a novel contribute to discussing and nuancing political, cultural, and human issues? Drawing on rhetorical fictionality theory, I focus on Korneliussen’s use of local fictionality, particularly in the form of death representations, composition, and pronominal shifts, demonstrating how she, trough the novel’s countdown structure, for instance, presents perspectives that seem inaccessible outside literature. I denne artikel analyserer jeg Niviaq Korneliussens behandling af den aktuelle grønlandske selvmordsproblematik i romanen Blomsterdalen (2020). Romanen er – efter forfatterens eget udsagn – «politisk», hvilket rejser en række spørgsmål: Hvorfor skrive en roman i stedet for et debatindlæg? Hvad er det for mulighedsrum, fiktionen åbner? Og på hvilke – og anderledes – måder kan en roman være med til at diskutere og nuancere politiske, kulturelle og menneskelige forhold? Med afsæt i retorisk fiktionalitetsteori fokuserer jeg på Korneliussens brug af lokal fiktionalitet i form af dødsrepræsentationer, komposition og pronominale skift og viser, hvordan hun, bl.a. gennem romanens nedtællingsspor, fremskriver perspektiver, der synes utilgængelige uden for litteraturens verden.